Formative Assessment Strategies of Senior High School Physics Teachers in Selected Ashanti Region Districts, Ghana - Michael Atibilla Akooba; George Oduro-Okyereh; Isaac Owusu-Mensah (Journal of Research in Education and Pedagogy, 2026)
The study examined the formative assessment strategies senior high school physics teachers in selected districts of the Ashanti Region practice in their classrooms. Using a descriptive survey design, the study purposively selected 108 physics teachers from 36 senior high schools across nine districts. Data were collected through a 21-item closed-ended questionnaire and an observation guide. Descriptive statistics such as mean, standard deviation, and percentage were used to analyse the research question, while an independent samples t-test was used to test the hypothesis at a significance level of (α = 0.05). The results revealed that physics teachers in the Ashanti Region employ diverse formative assessment strategies to support students’ learning. These include clarifying learning objectives, providing timely feedback, using varied assessment tasks, and offering suggestions for improvement. However, peer and self-assessment practices were found to be infrequently implemented. Furthermore, the study established a statistically significant difference between more experienced teachers (those with at least five years of service) and less experienced teachers (serving less than five years), with the former employing diverse formative assessment strategies. The findings suggest that teaching experience enhances teachers’ ability to apply varied formative assessment approaches effectively. The recommendation for this study suggests that the Ghana Education Service should organize professional development programmes focused on formative assessment practices for less experienced teachers to strengthen their classroom assessment literacy and improve instructional quality. The study enhances the comprehension of subject-specific formative assessment practices and underscores the need for continuous professional learning to promote effective physics teaching and learning in senior high schools.